2019
DOI: 10.1097/qad.0000000000002150
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal insulin therapy reverses hippocampal dendritic injury and cognitive impairment in a model of HIV-associated neurocognitive disorders in EcoHIV-infected mice

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 72 publications
(117 reference statements)
11
68
0
Order By: Relevance
“…Intranasal insulin therapy in preclinical studies using Eco HIV-infected mice have been shown to improve cognition through upregulation of BDNF levels. 84 A clinical trial is presently being done by Sacktor et al to assess safety and efficacy in HAND. 85…”
Section: Intranasal Insulin Therapymentioning
confidence: 99%
“…Intranasal insulin therapy in preclinical studies using Eco HIV-infected mice have been shown to improve cognition through upregulation of BDNF levels. 84 A clinical trial is presently being done by Sacktor et al to assess safety and efficacy in HAND. 85…”
Section: Intranasal Insulin Therapymentioning
confidence: 99%
“…EcoHIV Detectable viral load in the brain, neuroinflammation, loss of MAP-2 and synapsin II staining [179,337] Impaired working and spatial memory [179,181,182] Non-rodent animal models SIV infected macaques Depletion of CD4+ cells, detectable viral load in the brain, neuroinflammation, neuronal loss [162] Impaired performance in tasks assessing memory, fine/ general motor skills, motivation, reaction time, spatial working memory [338] FIV infected cats Encephalopathy, reduced peripherical and motor neuron conductance [206,207] Aggression, loss of socialization, gait changes [206,207] mice developed age-specific memory deficits and the model helped to delineate cellular pathways involved in gp120 mediated neurotoxicity [167,168]. Similarly, a Tat transgenic mouse model was also developed where Tat is expressed under the control of a doxycycline-dependent GFAP promoter, allowing for these mice to develop Tat-dependent brain pathologies such as astrogliosis, infiltration of monocytes/T-cells and premature death [169].…”
Section: Chimeric Virusesmentioning
confidence: 99%
“…Others have shown that inoculation with EcoHIV at a dose of 1 × 10 6 pg p24 through intraperitoneal (IP) injection leads to the same behavioural impairments as early as 1 month post infection [180][181][182].…”
Section: Chimeric Virusesmentioning
confidence: 99%
“…Increasing insulin in the brains of mice has cognitive and pathological benefits in neurodegenerative models (Chen et al, 2017;Kim et al, 2019;Sanguinetti et al, 2019). Clinical trials of intranasal insulin administration to combat dementia and AD are currently ongoing with mixed results to this point (Avgerinos et al, 2018).…”
Section: Brain Insulin Receptor and Insulin Resistance In Diabetes mentioning
confidence: 99%